Hippocampal dysgenesis and variable neuropsychiatric phenotypes in patients with Bardet-Biedl syndrome underline complex CNS impact of primary cilia - Bennouna-Greene, V; Kremer, S; Stoetzel, C; Christmann, D; Schuster, C; Durand, M; Verloes, A; Sigaudy, S; Holder-Espinasse, M; Godet, J; Brandt, C; Marion, V; et al. (Clinical genetics, 2011)
Bennouna‐Greene V, Kremer S, Stoetzel C, Christmann D, Schuster C, Durand M, Verloes A, Sigaudy S, Holder‐Espinasse M, Godet J, Brandt C, Marion V, Danion A, Dietemann J‐L, Dollfus H. Hippocampal dysgenesis and variable neuropsychiatric phenotypes in patients with Bardet–Biedl syndrome underline complex CNS impact of primary cilia. The Bardet–Biedl syndrome (BBS) is a rare ciliopathy clinically defined by the association of retinitis pigmentosa, polydactyly, obesity, kidney disease and cognitive impairment. The cognitive functioning, behavioral phenotype, prevalence of psychiatric diseases and memory performances of a cohort of 34 patients with BBS were evaluated and a systemic brain magnetic resonance imaging (MRI) was performed. The patients' cognitive functioning was of marked variable efficiency ranging from normal to disabling performances. Neuropsychological disorders such as slow thought process, attention difficulties and obsessive‐compulsive traits were observed. Our main finding was hippocampal dysgenesis, diagnosed by MRI, found in 42.31% of the patients in this cohort. Moreover, we show that BBS proteins are expressed in the human hippocampus and in the human brain in the normal subject. Recent literature in the murine model shows that hippocampal neurogenesis, in particular in the adult mouse, requires an intact primary cilia. These results encourage us to further investigate the possible role of BBS proteins in the hippocampus and related central nervous system structures.